URGENSI LAYANAN KONSELING BAGI WANITA BINAAN (STUDI DI LEMBAGA PEMASYARAKATAN KELAS III SIGLI) - Latif, Umar; Syarif, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Providing counseling services for assisted women in LP is a very important thing. Problems faced by women in Class III LP Sigli, such as feeling depressed because they are far away from their children, husband and family, and so forth. So in this study, researchers focus on why counseling services are very important to be provided, how the form of counseling services and the effectiveness of the implementation of counseling services for women in prison in Class III prisons Sigli. This qualitative research collected data using observation, interview and documentation methods. The results of the study found that psychological problems of household life of fostered residents in Sigli Class III Correctional Institution are unhealthy mental conditions of fostered residents such as anxiety, anxiety, feelings of guilt and regret, and because of losing various important things in his life, especially those related to his family while they served their sentences at the Penitentiary. Handling of psychological problems in the lives of fostered households is adjusted to the guidance of Islamic teachings by paying attention to the problems faced by clients. Handling is done by helping clients increase their knowledge, understanding and practice of religion and try to involve the counselor from outside, such as the cleric or teungku to fill routine recitals or lectures that are able to arouse the spirit of life and comfort after participating in the study. Counseling services have been done well and maximally at Sigli Class III Women's Penitentiary and of course it can be said to be running effectively, even though there are still some technical obstacles in its implementation. But in general, can be said to be effective.Keywords: Counseling, Assisted Women and Correctional Institutions.